Saturday

April 19, 2014

April 19, 2014

Posted by **Eric** on Wednesday, April 24, 2013 at 4:09pm.

log(7x + 4) = 2 + log(2x − 3)

Solve the equation.

log(x^3) = (log x)^2

- Math -
**Reiny**, Wednesday, April 24, 2013 at 6:14pmlog(7x + 4) = 2 + log(2x − 3)

log(7x + 4) - log(2x − 3) = 2

log( (7x+4)/(2x-3) ) = 2

(7x+4)/(2x-3) = 10^2 = 100

200x - 300 = 7x+4

193x = 304

x = 304/193 or appr 1.575

for the 2nd

log x^3 = log x^2

x^3 = x^2

x^3 - x^2 = 0

x^2(x-1) = 0

x = 0 or x = 1

but from log(2x-3) , 2x-3 > 0

2x > 3

x > 3/2

so there is not solution.

**Related Questions**

exact logarithms - Use the properties of logarithms to find the exact value of ...

Math - Properties of Logarithms - Use properties of logarithms to find the exact...

trigonometry - Use logarithms and the law of tangents to solve the triangle ABC...

Logarithms - Use the properties of logarithms to find the exact value of the ...

Logarithms - What's the fastest way to find Anti Logarithms(not using ...

Logarithms - What's the fastest way to find Anti Logarithms(not using ...

Logarithms - What's the fastest way to find Anti Logarithms(not using ...

trigonometry - okay so i have this trigonometry problem were i HAVE to use ...

Math - Solve for x. 14^(-3x)=11^(-x-3) Write the exact answer using base-10 ...

Pre-Calculus - The exponential function y(x)=Ce^ax satisfies the conditions y(0...